Nucleophilicities and Lewis Basicities of Sterically Hindered Pyridines - Follet, Elsa; Zipse, Hendrik; Lakhdar, Sami; Ofial, Armin R.; Berionni, Guillaume (Synthesis, 2017)
The structures of the covalent Lewis adducts and/or frustrated Lewis pairs derived from 2- and 2,6-substituted pyridines with diaryl (Ar2CH+) and with the more bulky triaryl (Ar3C+) carbenium ions were analyzed by UV-vis and NMR spectroscopy. Thermodynamics (equilibrium constants) and kinetics (rate constants) of the associations of the carbon-centered Lewis acids Ar2CH+ with a series of sterically hindered pyridines were investigated and used for the determination of the Lewis basicities and nucleophilicities, on the basis of the Mayr electrophilicity/nucleophilicity and Lewis acidity/basicity linear free energy relationships. In addition, methyl and benzhydryl cation affinities were computed to elucidate the respective steric and electronic contributions of the substituents to the nitrogen atom Lewis basicity. The influence of the size of the reference carbenium ion on the magnitude of the repulsion induced by the pyridine substituents (Me, tBu in 2- or 2,6-positions) was also analyzed. Cumulated steric repulsion was found to decrease the reactivity of the nitrogen atom by up to 10 orders of magnitude.
Keywords: pyridines; Lewis bases; Lewis adducts; frustrated Lewis pairs; reactivity scales; nucleophilicities